دور الخامات في رفع القيمة الوظيفية والمظهرية في التصميم الداخلي للمباني السكنية (Comprehensive Journal of Science, 2025)
The selection of materials in interior design is one of the fundamental factors influencing the balance between functional and aesthetic aspects of residential buildings. Materials serve as visual and tactile elements that enhance user comfort and express the identity of interior spaces. The significance of this research lies in exploring the role of materials in enhancing the functional and aesthetic value of interior design through analyzing the relationship between material quality and its impact on both usability and visual appeal within residential environments.The research problem stems from the limited awareness among some designers and users regarding the importance of integrating materials in a way that considers both their physical and aesthetic properties. This often leads to a deficiency in functional performance or a lack of visual harmony in interior spaces.Accordingly, the study seeks to answer the following key questions:What role do materials play in achieving functional comfort within residential buildings?How does the type and finish of a material contribute to enhancing the aesthetic value of housing interiors?What are the optimal design criteria for selecting materials that ensure integration between function and aesthetics?The research adopts a descriptive-analytical approach by examining selected residential architectural models and analyzing the properties of materials used in terms of texture, color, light reflection, and maintenance efficiency.The findings indicate that a conscious and integrated selection of materials significantly enhances users’ psychological and visual comfort, improves spatial functionality, and reinforces the design identity with a distinctive and sustainable character.The study recommends adopting comprehensive design criteria for material selection that consider technical, aesthetic, and environmental aspects. It also emphasizes the importance of using sustainable materials with high performance and enduring aesthetic qualities. Furthermore, it encourages more applied studies that link material science with user behavior in residential interior spaces.
Keywords: Materials – Interior Design – Residential Buildings – Functional Value – Aesthetic Quality – Visual Comfort – Sustainable Materials.